The Nd:YAG dual-channel laser system with Q - modulation for direct interference lithography - Marczak, Jan Andrzej; Rycyk, Antoni; Sarzyński, Antoni; Strzelec, Marek; Czyż, Krzysztof (Photonics Letters of Poland, 2014)
A dual-channel laser system consisting of an Nd:YAG generator with Q - modulation and a "p – branch" type unstable resonator has been presented in the article. The laser assembly has been configured in such a way to constitute the arms of a Mach-Zehnder interferometer. The regulation of the amplification coefficient in both amplifying channels allows for quick and easy changes of the output energy in each channel up to the value of approximately 1.5 J, with the laser pulse duration of 8-10 ns. The Mach-Zehnder configuration of the interference assembly allowed for quick and easy changes of the angle between the interfering laser beams. Full Text: PDF References D. Xia, Z. Ku, S.C. Lee. and S.R.J. Brueck, S.R.J., "Nanostructures and Functional Materials Fabricated by Interferometric Lithography", Adv. Mater. 23, 147 (2011). CrossRef B. Raeymaekers, E. Izhak and F.E. Talka, "Enhancing tribological performance of the magnetic tape/guide interface by laser surface texturing", Tribol. Lett. 27, 89 (2007). CrossRef F. Mucklich, A. Lasagni and C. Daniel, "Laser interference metallurgy—periodic surface patterning and formation of intermetallics", Intermetallics 13, 437 (2005). CrossRef R. Major, K. Maksymow, J. Marczak, J.M. Lackner, M. Kot and B. Major, Bull. Pol. Acad. Sci-Te. 60, 337 (2012). DirectLink J. Marczak, A. Rycyk, A. Sarzyński, M. Strzelec, J. Kusiński and R. Major, "Direct laser manufacturing of 1D and 2D micro- and submicro-scale periodic structures ", Proc. SPIE 8703, 87030F (2013). CrossRef C. Daniel,J. Drummond and R. A. Giordano, "Improving Flexural Strength of Dental Restorative Ceramics Using Laser Interference Direct Structuring", J. Am. Ceram. Soc. 91 3455 (2008). CrossRef N. Ganesh, I.D. Block and B.T. Cunningham, "Near ultraviolet-wavelength photonic-crystal biosensor with enhanced surface-to-bulk sensitivity ratio", Appl. Phys. Lett. 89, 023901 (2006). CrossRef H. Yu, O. Balogun, B. Li, T.W. Murray and X. Zhang, "Building embedded microchannels using a single layered SU-8, and determining Young’s modulus using a laser acoustic technique", J. Micromech. Microeng. 14, 1576 (2004). CrossRef W.H. Ryu, S.W. Min, K.E. Hammerick, M. Vyakarnam, R.S. Greco, F.B. Prinz and R.J. Fasching, Biomaterials 28, 1174 (2007). CrossRef F.B. Prinz. and R.S. Smith, Nanoscale Technology in Biological Systems (Boca Raton, CRC Press 2005). CrossRef J. Zhang et al. "Combined topographical and chemical micropatterns for templating neuronal networks", Biomaterials 27, 5734 (2006). CrossRef I.B. Divliansky et al., "Fabrication of two-dimensional photonic crystals using interference lithography and electrodeposition of CdSe", Appl. Phys. Lett. 79, 3392 (2001). CrossRef J. Marczak, Invited Presentation. Laser interference patterning of DLC layers for directed migration and growth of smooth muscle cell depositions. EMRS 2013 Fall Meeting, 16-20 Sept. 2013: DirectLink